PENGENALAN KONSEP ETNOMATEMATIKA MELALUI KEGIATAN EKSPLORASI BUDAYA LOKAL BANYUWANGI - Masruroh, Farhatin; Ulfah, Maulidya; Khulusinniyah; Soliha, Umdatus (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah Universitas Ibrahimy, 2023)
The introduction of ethnomathematics concepts through this exploration activity is very important to be applied to Early Childhood Education institutions. Because this activity aims to improve the ability to learn mathematics and culture in children, children must be introduced to ethnomathematics learning from an early age. This study uses Action Research with 2 cycles through planning, observation, implementation, and action procedures. The formulation of the problems in this study are: 1) How is the introduction of ethnomathematics concepts through Banyuwangi local cultural exploration activities 2) What are the results of the introduction of ethnomathematics concepts through Banyuwangi local cultural exploration activities, While the results of the study: 1) The process carried out is that children carry out mathematical exploration activities with objects typical of Banyuwangi culture with varied activities. 2) Research results In the pre-cycle the percentage of children was 35% and after the action was carried out in cycle I only 11 children out of a total of 17 children were declared able to achieve the minimum completeness criteria, with a percentage of 65%. Whereas in cycle II there were 14 children who had succeeded in achieving the minimum completeness criteria with a percentage of 82%. Based on the results of cycle II, it was not continued in the next cycle because it had reached the set classical completeness target, namely 80%.